Rapidly mutating Y-STRs in rapidly expanding populations: Discrimination power of the Yfiler Plus multiplex in northern Africa. (January 2019) - D'Atanasio, Eugenia; Iacovacci, Giuseppe; Pistillo, Rossella; Bonito, Maria; Dugoujon, Jean-Michel; Moral, Pedro; El-Chennawi, Farha; Melhaoui, Mohammed; Baali, Abdellatif; Cherkaoui, Mohamed; Sellitto, Daniele; Trombetta, Beniamino; et al.
Graphical abstract: Highlights: The Y-STR profiles of 477 northern African males were obtained using the 27-loci Yfiler® Plus kit. About 46% of the samples belonged to the recent E-M81 Y haplogroup. The AMOVA analysis showed significant differences between populations and countries. The number of identical Y-STR profiles was drastically reduced using the Yfiler® Plus compared to Yfiler. Abstract: The male-specific northern African genetic pool is characterised by a high frequency of the E-M81 haplogroup, which expanded in very recent times (2–3 kiloyears ago). As a consequence of their recent coalescence, E-M81 chromosomes often cannot be completely distinguished on the basis of their Y-STR profiles, unless rapidly-mutating Y-STRs (RM Y-STRs) are analysed. In this study, we used the Yfiler® Plus kit, which includes 7 RM Y-STRs and 20 standard Y-STR, to analyse 477 unrelated males coming from 11 northern African populations sampled from Morocco, Algeria, Libya and Egypt. The Y chromosomes were assigned to monophyletic lineages after the analysis of 72 stable biallelic polymorphisms and, as expected, we found a high proportion of E-M81 subjects (about 46%), with frequencies decreasing from west to east. We found low intra-population diversity indexes, in particular in the populations that experienced long-term isolation. The AMOVA analysis showed significant differences between the countries and between most of the 11 populations, with a rough differentiation between northwestern Africa and northeastern Africa, where the Egyptians Berbers from Siwa represented an outlier population. The comparison between the Yfiler® and the Yfiler® Plus network of the E-M81 Y chromosomes confirmed the high power of discrimination of the latter kit, thanks to higher variability of the RM Y-STRs: indeed, the number of chromosomes sharing the same haplotype was drastically reduced from 201 to 81 and limited, in the latter case, to subjects from the same population.